Potensi Pemanfaatan Limbah Plastik HDPE Sebagai Bahan Aditif untuk Meningkatkan Kinerja Perkerasan AC-BC - Karyawan, I Dewa Made Alit; Widianty, Desi; Febriana, Arlin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Flexible pavement construction widely employs asphalt as the primary binding material due to its ability to coat aggregates and form a strong, cohesive structure. However, the growing demand for asphalt and rising prices driven by global oil market fluctuations pose significant challenges to its availability. Therefore, alternative solutions are needed to reduce reliance on pure asphalt while enhancing the performance of asphalt mixtures. One promising alternative is the utilization of waste plastic in the form of High Density Polyethylene (HDPE), which has been shown to improve mixture stability, resistance to permanent deformation (rutting), and durability against moisture damage, while also contributing to sustainable waste management. This study aims to evaluate the effect of HDPE addition on the characteristics of Asphalt Concrete - Binder Course (AC-BC) mixtures. Based on the volumetric and mechanical analysis of the AC-BC mixture, adding HDPE increases stability and density with a decrease in VMA and VIM and an increase in VFA. Stability increases significantly up to 12%, but flow exceeds the specification limit at a content of ≥8%, and the Marshall Quotient decreases, indicating a decrease in stiffness. According to the Bina Marga specification (2018), the maximum HDPE content meets the requirements is 4%. A multi-criteria approach is needed to determine the best HDPE content that balances strength, flexibility, and long-term deformation resistance